2021
DOI: 10.1039/d1dt03134a
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic chemistry and application of palladacycles in asymmetric hydrophosphination reactions

Abstract: A number of palladacycles containing chiral chelating auxiliaries have been utilized as efficient catalysts for asymmetric hydrophosphination reactions. In all cases, the chiral auxiliaries remained coordinated to the palladium centres...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…In principle, asymmetric HP is an incredibly powerful synthetic route to access the next generation of chiral phosphine ligands. This area of HP has been dominated by palladium complexes bearing chiral chelating auxiliaries. However, there have been early examples of nickel-catalyzed , and organocatalytic asymmetric HP. More recently Wang and co-workers reported the asymmetric HP of numerous azabenzonorbornadiene and oxabenzonorbornadiene substrates with different secondary biarylphosphines mediated by palladium precatalyst and Fe­(OAc) 2 as a substoichiometric additive (Scheme ).…”
Section: Hydrophosphinationmentioning
confidence: 99%
“…In principle, asymmetric HP is an incredibly powerful synthetic route to access the next generation of chiral phosphine ligands. This area of HP has been dominated by palladium complexes bearing chiral chelating auxiliaries. However, there have been early examples of nickel-catalyzed , and organocatalytic asymmetric HP. More recently Wang and co-workers reported the asymmetric HP of numerous azabenzonorbornadiene and oxabenzonorbornadiene substrates with different secondary biarylphosphines mediated by palladium precatalyst and Fe­(OAc) 2 as a substoichiometric additive (Scheme ).…”
Section: Hydrophosphinationmentioning
confidence: 99%
“…of Ph2PH and 5 mol % of (N2O)ZrBn3 (1) at ambient temperature under visible light irradiation to afford 83% conversion to the corresponding hydrophosphination product in 2 h (Table 1, Entry 9). Trans-chalcone, a typical model substrate in asymmetric hydrophosphination [29,30], showed 68% conversion in a modest 24 h period (Table 1, Entry 10).…”
Section: Photocatalytic Hydrophosphinationmentioning
confidence: 99%
“…A wide range of phosphine chemistry has been developed, with metal catalyzed hydrophosphination being one of the most economic avenues for P-C bond formation. Though significant progress has occurred [1,7,[15][16][17][18][19][20][21][22][23][24], challenges remain for this transformation, with catalyst and substrate scope being two key avenues for improvement [1,15,[25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Chiral palladium( ii ) pincer complexes, which contain chiral meridionally coordinated terdentate ligands, have succeeded in acting as effective and stereoselective catalysts for a broad variety of asymmetric reactions such as Michael addition, aldol type condensation, allylation reaction, hydrophosphination, Friedel–Crafts reaction of indoles, as well as reactions of nitrile compounds with sulfonimines or nitroalkenes. 1 For example, Uozumi and co-workers reported that the bis(pyrroloimidazolone) NCN pincer Pd complex A (Chart 1) was a viable catalyst for asymmetric Michael addition of 2-cyanopropionates to vinyl ketones with enantioselectivities up to 83% ee. 2 Szabó and co-workers found that the axially chiral bis(phosphite) PCP Pd pincer catalyst B exhibited good stereoselectivities in the allylation of sulfonimines (up to 85% ee) 3 a and aldol condensation of sulfonimines with isocyanoacetate (up to 86% ee).…”
Section: Introductionmentioning
confidence: 99%